Multiattribute ranking based on analytic hierarchy model - Wei WANG; Tie-jun ZHAO; Guo-dong XIN; Bing XU (Tongxin xuebao)
An approach based on analytic hierarchy model for solving product multiattribute ranking was proposed.The approach decomposed a decision problem into hierarchy of more easily comprehended sub-problems,such as goal level,criteria level,and alternative level.Then priorities among the elements of the hierarchy were established towards its higher hierarchy.Synthesize these priorities to yield a set of overall iorities for the alternative hierarchy by using weighted sums.The experiment results show the effectiveness of analytic hierarchy model.